Analisis Faktor Risiko Diabetes Mellitus Tipe 2 berdasarkan Rekam Medis Rawat Inap di RS Citra Husada Jember - Indah Feby Kusuma Wardani; Ervina Rachmawati; Novita Nuraini; Efri Tri Ardianto (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2025)
The number of inpatients at Citra Husada Hospital with type 2 DM continues to increase every year until 2023, there were 734 patients. The purpose of this study was to examine how gender, a history of obesity, and a history of hypertension relate to risk factors for type 2 diabetes. Based on medical record data from inpatients at Citra Husada Hospital in 2023, this study sought to examine the association between the occurrence of type 2 DM and risk variables for the disease, including gender, history of obesity, and history of hypertension. This kind of study used secondary data in analytic observational case control methodology. Using basic random sampling, 133 case samples and 133 control samples made up the study sample. descriptive analysis for univariate data analysis and the chi-square test for bivariate data analysis. The results showed variables associated with Type 2 DM, namely a history of obesity (p = 0.000) with a risk of 3.297 times developing Type 2 DM and a history of hypertension (p = 0.020) with a risk of 1.836 times developing Type 2 DM and unrelated variables, namely Gender (p = 0.376).